Peran Guru Sebagai Motivator dalam Membentuk Karakter Tanggung Jawab pada Siswa Kelas V SDN 85 Kota Bengkulu - Apriwani, Septa; Parmadi, Bambang; Tarmizi, Pebrian (UNIB Press, 2025)
This study aims to describe the role of teachers as motivators in forming a character of responsibility in 5th grade students at SDN 85 Bengkulu City. This study uses a qualitative approach with a descriptive method. The subjects of the study consisted of 5th grade teachers and 22 students, consisting of 9 male students and 13 female students. To collect data, this study used instruments in the form of observation guidelines, interviews, and documentation. Data collection techniques include observation, interviews with teachers and students, and documentation. The data obtained were analyzed through four stages, i.e. data collection, data condensation, data presentation, and drawing conclusions. The results of the study showed that teachers tried to be a motivator by implementing various strategies, such as using various learning methods, creating a competitive atmosphere both individually and in groups, and giving praise to students who achieved good learning outcomes. However, it was found that the role of teachers in giving rewards and punishments had not been seen significantly. Based on the results of the study, it can be concluded that teachers play an active role as motivators in instilling the value of responsibility in students. Through the approach applied, teachers encourage students to be more responsible in carrying out their duties and obligations. Thus, the character of responsibility formed in students cannot be separated from the role of the teacher as a motivator.